KEBERLANJUTAN BELAJAR MEMBACA SISWA SEKOLAH DASAR DI LUAR WAKTU SEKOLAH DI LOMBOK TIMUR - Zulfadli Hamdi; Khirjan Nahdi; Baiq Zuriatun Hasanah; Muhammad Husni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Continuity of reading practice beyond school hours is essential for strengthening the literacy skills of primary school students through the connection of learning experiences between school and home. This study aims to describe the continuity of students' reading practice after school hours, the role of teachers in directing home reading activities, and parental support for children's reading practice. The urgency of this study is grounded in the need to build a consistent reading habit amid the tendency for after-school time to be dominated by play and digital device use. The novelty of this study lies in the analysis of the continuity gap among teacher assignments, student reading practice, and family support as a single learning sequence across spaces. This study used a descriptive qualitative design in two primary education units in East Lombok. Informants consisted of two teachers, ten students, and ten parents or guardians. Data were obtained through interviews, observation, and documentation, then analyzed through data condensation, data display, pattern identification, and cross-source verification. The results show three main findings. First, home reading activity occurs sporadically and has not yet developed into a daily habit. Second, teachers have provided reading assignments and guidance with varying frequency, form, monitoring, and follow-up across classes. Third, parents provide motivation, reminders, assistance, and facilities with varying intensity. This study concludes that the continuity of reading practice requires a more systematic connection among school assignments, student routines, family assistance, and teacher feedback. Keywords: learning continuity, reading, primary school students, teacher's role, parents' role